Bangladesh at 25 : an analytical discourse on development - Bayes, Abdul; Ānu Muhāmmada (University Press Ltd., 1998)
Papers presented at a seminar organized by the Jahangirnagar University in 1995 to observe 25 years of Bangladesh.